Influence of Resin Viscosity on Physical Properties of a Composite Shell Wound on a Low Density Material Mandrel - Sinha, Surjeet kumar; Buragohain, Manoj Kumar; Bose, P Subhash Chandra (Defense science journal, 2024)
This study is made to improve the structural performance of composite shells/ vessels meant for aerospace vehicles. The effect of resin viscosity on the physical properties of carbon/ epoxy composite shell wound on polyurethane (PU) foam-based mandrel is studied and presented in this paper. Cylindrical shells were manufactured through the filament winding process at different resin viscosities. The physical properties of the composite shell are found to be improved significantly with a reduction in resin viscosity. Resin pick-up in impregnated fibers is found to be lower by 4.5 %, whereas mass and thickness of the shells are recorded to be lower by 3 % and 5.4 % respectively at resin viscosity range of 600 -760 mPa.s compared to the viscosity range of 1380 – 2080 mPa.s. Fiber volume fraction and density of composite shell are found to be higher by 6.3 % and 2.8 % at the same resin viscosity range. This trend reverses/stabilizes after further heating and corresponding lowered resin viscosity. Experiment and their result indicate an optimal viscosity range of 600 – 760 mPa.s. for filament winding of efficient carbon/ epoxy composite shell